Controlled CO labilization of tungsten carbonyl precursors for the low-temperature synthesis of tungsten diselenide nanocrystals - Geisenhoff, Jessica Q.; Yin, Hang; Oget, Natacha; Chang, Haeun; Chen, Linfeng; Schimpf, Alina M. (Frontiers in Nanotechnology, 2022)
We report a low-temperature colloidal synthesis of WSe2 nanocrystals from tungsten hexacarbonyl and diphenyl diselenide in trioctylphosphine oxide (TOPO). We identify TOPO-substituted intermediates, W(CO)5TOPO and cis-W(CO)4(TOPO)2 by infrared spectroscopy. To confirm these assignments, we synthesize aryl analogues of phosphine-oxide-substituted intermediates, W(CO)5TPPO (synthesized previously, TPPO = triphenylphosphine oxide) and cis-W(CO)4(TPPO)2 and fac-W(CO)3(TPPO)3 (new structures reported herein). Ligation of the tungsten carbonyl by either the alkyl or aryl phosphine oxides results in facile labilization of the remaining CO, enabling low-temperature decomposition to nucleate WSe2 nanocrystals. The reactivity in phosphine oxides is contrasted with syntheses containing phosphine ligands, where substitution results in decreased CO labilization and higher temperatures are required to induce nanocrystal nucleation.